2021
DOI: 10.1182/bloodadvances.2020004094
|View full text |Cite
|
Sign up to set email alerts
|

The potential of proliferative and apoptotic parameters in clinical flow cytometry of myeloid malignancies

Abstract: Standardization of the detection and quantification of leukocyte differentiation markers by the EuroFlow Consortium has led to a major step forward in the integration of flow cytometry into classification of leukemia and lymphoma. In our opinion, this now enables introduction of markers for more dynamic parameters, such as proliferative and (anti)apoptotic markers, which have proven their value in the field of histopathology in the diagnostic process of solid tumors and lymphoma. Although use of proliferative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…Notably, the markers recommended only identify those that have been validated in a multicenter setting. Several studies have introduced markers that may be of additive value, either as a single marker, in combination with a diagnostic mini‐panel or in combination with other markers (Alayed et al, 2020 ; Della Porta et al, 2012 ; Mestrum et al, 2021 ; Shameli et al, 2020 ).…”
Section: Panelmentioning
confidence: 99%
“…Notably, the markers recommended only identify those that have been validated in a multicenter setting. Several studies have introduced markers that may be of additive value, either as a single marker, in combination with a diagnostic mini‐panel or in combination with other markers (Alayed et al, 2020 ; Della Porta et al, 2012 ; Mestrum et al, 2021 ; Shameli et al, 2020 ).…”
Section: Panelmentioning
confidence: 99%
“…Effects of treatment modalities for myeloid malignancies can be predicted based on the proliferative and anti‐apoptotic capacity in the different hematopoietic cell lineages [11]. Erythroblasts are found to be highly proliferative and, hence, therapies that counter‐act on proliferating cells (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of proliferative and apoptotic markers in establishing a better prognosis and prediction of treatment response in myeloid malignancies was studied in the past decades [11], but this did not lead to the incorporation of the intracellular dynamic markers in the diagnostic work-up of these malignancies. The number of parameters that could be analyzed by histopathological and flow cytometric analyses was limited at the time that these markers were initially studied.…”
Section: Introductionmentioning
confidence: 99%
“…Annexin V/FITC assay estimates the number of cells that undergo apoptosis. This method discriminate to discrimination between viable, apoptosis, and necrotic cells 31 . When individual drugs were evaluated for % of apoptotic cells, it was observed that at 24 and 48 hrs the number of apoptotic cells was more compared to the control cells.…”
Section: Cell Cycle Assaymentioning
confidence: 99%